2008
DOI: 10.1002/jrs.2106
|View full text |Cite
|
Sign up to set email alerts
|

Study on the applied limitation of the micro‐crystal model for Raman spectra of nano‐crystalline semiconductors

Abstract: The limitation in sample size and the choice in parameters for the application of the micro-crystal (MC) model have been tested and discussed. The testing was performed through the fitting of calculated Raman spectra by using the MC model with the observed Raman spectra for nearly uniform-sized nanocrystalline (NC)-Si of smaller than 2 nm. The results showed that the good fittings could not be obtained, if the phonon dispersion curves !.q/ and Raman linewidths 0 of bulk-crystals (BCs) were used, i.e. if the bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…6(d) and 6(e). The broadening of the A 1 1g and A 2 1g peaks with decreasing thickness follows the phenomenological exponential relationship 0 (d) = A + B exp(−d/C), where d represents the thickness of the Bi 2 Te 3 nanoplates, and A, B, and C are fitting parameters [15,42]. Good fitting was achieved with A = 2.4 ± 0.08, B = 33.9 ± 7.9, and C = 1.1 ± 0.1 for A 1 1g and A = 7.6 ± 0.03, B = 46.0 ± 7.4, and C = 0.9 ± 0.05 for A 2 1g , as shown by the blue solid lines in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6(d) and 6(e). The broadening of the A 1 1g and A 2 1g peaks with decreasing thickness follows the phenomenological exponential relationship 0 (d) = A + B exp(−d/C), where d represents the thickness of the Bi 2 Te 3 nanoplates, and A, B, and C are fitting parameters [15,42]. Good fitting was achieved with A = 2.4 ± 0.08, B = 33.9 ± 7.9, and C = 1.1 ± 0.1 for A 1 1g and A = 7.6 ± 0.03, B = 46.0 ± 7.4, and C = 0.9 ± 0.05 for A 2 1g , as shown by the blue solid lines in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Raman spectra of nanocrystal semiconductors usually exhibit new features that are different from those of the corresponding bulk-crystalline semiconductors. A study on the limitation of a micro-crystal model for describing Raman spectra of such nanocrystalline semiconductors was reported by Zhang et al [202] Thermo-Raman spectroscopy was used by Zhao et al [203] to study the transition of micro-sized α-GaO(OH) to β-Ga 2 O 3 rods. Observed vibrational bands were assigned.…”
Section: Nanoparticles Nanowires/rods and Nanocrystalline Thin Filmsmentioning
confidence: 99%
“…From the fitting, it was found that the MC model is invalid for Si crystallites smaller than ∼4 nm with nearly uniform size if the dispersion curve ω( q ) and linewidth г( q ) are chosen based on the bulk-like approximation (BLA), and the characteristics of the dispersion curve and Raman linewidth appearing in the best fit are different from those predicted by the BLA. 6…”
Section: Introductionmentioning
confidence: 99%
“…From the fitting, it is found that the MC model is invalid for Si crystallites smaller than ∼4 nm with nearly uniform size if the dispersion curve ω( q ) and linewidth r ( q ) are chosen based on the BLA, and the characteristics of the dispersion curve and Raman linewidth appearing in the best fit are different from those predicted by the BLA. 114 In recent years, they have mainly carried out research upon the Raman spectra of nanostructured semiconductors and carbon nanotubes, as well as the MP Raman spectra of ZnO nanoparticles. The reliability of the optical model Raman frequency with size-independent phenomena of single-phonon and MP in polar semiconductors such as ZnO was demonstrated.…”
Section: Introductionmentioning
confidence: 99%